UJI ANGKA KAPANG KHAMIR DALAM PRODUK PANGAN DI BALAI PENGAWAS OBAT DAN MAKANAN DI KUPANG - Serly Benufinit; Nur Aini Bunyani, Maya F. Roman; Fadhila P. Imananta (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2025)
Food is anything that comes from biological sources and water. Mold and Yeast Numbers are Quantitative Methods used to determine the number of molds and yeasts in a sample. This study has been conducted with the aim of Determining Microbial contamination in the form of Molds, Yeasts in Seasoned Flour samples. The next objective is to determine the results of the test for Microbial contamination of Molds, Yeasts in Seasoned Flour in the Microbiology Laboratory according to the requirements of the Regulation of the Head of the Indonesian Food and Drug Supervisory Agency No. 12 of 2014. This study used the spread method, with samples weighed aseptically as much as 25 g in a suitable sterile container, then added 225 ml of PSS, homogenized to obtain a suspension with a dilution of 10-1. The results of this study indicate that the examination of the yeast mold number test in food products with sample code 10, was declared to meet the requirements (ms) with results <10 colonies/gram where the maximum requirement limit for the Yeast Mold Number (AKK) is 5x103 colonies/gram and is suitable for consumption